THE PREVENTIVE AND RESTORATIVE APPROACHES TO MANAGE DENTAL EROSION-INDUCED LESIONS, CONSIDERING MATERIALS AND TECHNIQUES TO RESTORE BOTH ESTHETICS AND FUNCTION - Robina Tasleem, Khalid M. Abdelaziz, Sumayyah Binte Adnan, Dr Tanzeel Ur Rehman, Dr Qurat ul Ain Khursheed, Ibtihag Siddig Elnaem Mohamed-Nour, Dr Fahmida Khatoon, Dr Harris Saeed ,Dr Madiha Rasheed (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Dental erosion, a common concern in contemporary dentistry, poses a significant challenge to both esthetics and function. This study addresses the need for effective preventive and restorative approaches to manage dental erosion-induced lesions, focusing on preserving and enhancing the esthetic and functional aspects of affected teeth.Aim: The primary objective of this research is to investigate and evaluate preventive measures and restorative techniques for dental erosion-induced lesions. By considering a range of materials and methodologies, the aim is to develop comprehensive strategies that address both esthetic concerns and functional restoration.Methods: A systematic literature review and experimental investigation were conducted to gather relevant information on preventive and restorative approaches to dental erosion. The review involved an in-depth analysis of existing studies, clinical trials, and case reports. Additionally, laboratory experiments were conducted to assess the performance of various materials and techniques in restoring both esthetics and function.Results: The findings reveal a spectrum of preventive measures, including lifestyle modifications, dietary counseling, and fluoride applications, to mitigate the impact of dental erosion. In the realm of restorative techniques, a variety of materials such as resin composites, glass ionomers, and ceramics were explored for their efficacy in esthetic and functional restoration. The results provide insights into the effectiveness of different approaches, aiding clinicians in making informed decisions based on the specific needs of individual cases.Conclusion: This study underscores the importance of a holistic approach to managing dental erosion-induced lesions, considering both preventive and restorative aspects. The integration of preventive measures alongside the judicious selection of restorative materials and techniques is crucial for achieving optimal esthetic and functional outcomes. Clinicians can use this comprehensive understanding to tailor treatment plans that address the unique challenges posed by dental erosion, thereby enhancing patient satisfaction and oral health.